Edaphic Controls on Sedge Invasion in a Tropical Wetland Assessed with Electromagnetic Induction. Issue 5 (20th September 2013) - Atwell, Melissa; Wuddivira, Mark; Gobin, Judith; Robinson, David
Abstract : Invasion of sedge in the wetlands of Trinidad is causing an increase in wetland dry season fires and a reduction in coastal pasture, adversely affecting the livelihoods of people living and working in the wetlands. The purpose of our research was to determine if soil properties and water quality could help to explain why the area of sedge is expanding. We conducted an observational study, using geophysical methods and standard sampling techniques to determine the relationship between grass and sedge zonation and soil properties and water quality. Our findings showed that both the electrical conductivity of the soil solution at saturation (ECe) and surface water electrical conductivity (ECw) were significantly higher ( P < 0.05) in sedge communities than in grass communities (mean ECe of sedge = 4.4 dS/m; mean ECe grass = 3.7 dS/m; mean ECw of sedge = 0.5 dS/m; mean ECw of grass = 0.2 dS/m). Our interpretation is that changes to the local hydrology by channelizing and levying rivers, reducing wetland flooding, is enhancing saline intrusion and facilitating the invasion of brackish water sedge species into non‐salt‐tolerant grassland areas.